Revisiting FR13A for submergence tolerance: beyond the SUB1A gene - Hussain, Waseem; Anumalla, Mahender; Ismail, Abdelbagi M.; Walia, Harkamal; Singh, Vikas Kumar; Kohli, Ajay; Bhosale, Sankalp; Bhardwaj, Hans (Oxford University Press, 2024)
Rice landrace FR13A is the original donor of the SUB1A gene. FR13A harbors hidden genetic variation that surpasses the submergence tolerance level of SUB1A. Here, we provide an overview of the unique features of FR13A associated with exceptional recovery ability that have been overlooked since the significant discovery of the SUB1 locus. We present a detailed overview of how to underpin the new genes associated with the recovery ability seen in FR13A. Finally, we propose a unique approach to develop rice cultivars that surpass submergence tolerance beyond the SUB1 locus from FR13A.